Resistensi Budaya Terhadap Integrasi Dan Interkoneksi Di Kalangan Pendidik Dan Masyarakat - Rini Nopita; Citra Solehati; Haris Riadi (Universitas Negeri Makassar, 2026)
The integration and interconnection of science, religious values, and local culture are inevitable in facing the challenges of globalization and scientific development. However, in practice, these efforts often encounter cultural resistance among both educators and the community. This study aims to analyze the forms of cultural resistance, the factors causing it, and its implications for the process of integration and interconnection in the context of education and social life. This research uses a qualitative approach with field study methods through in-depth interviews, observation, and documentation studies. The results indicate that cultural resistance emerges in the form of conservative attitudes, concerns about the loss of cultural and religious identity, and a poor conceptual understanding of integration and interconnection. The main factors influencing this resistance include educational background, normative religious understanding, and the strong influence of local traditions. This study concludes that cultural resistance is not merely rejection, but rather a reflection of the need for an integration approach that is contextual, dialogical, and sensitive to the cultural and religious values of the community.